The Credit Crisis: Conjectures about Causes and Remedies - Diamond, Douglas W; Rajan, Raghuram G (American Economic Review, 2009)
What caused the financial crisis that is sweeping across the world? What keeps asset prices and lending depressed? What can be done to remedy matters? While it is too early to arrive at definite answers to these questions, it is certainly time to offer informed conjectures, and these are the focus of this paper.